2020
DOI: 10.1007/s11010-020-03806-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dimorphic moderate hypoglycemia preconditioning effects on Hippocampal CA1 neuron bio-energetic and anti-oxidant function

Abstract: Hypoglycemia is a detrimental complication of rigorous management of type 1 diabetes mellitus. Moderate hypoglycemia (MH) preconditioning of male rats partially affords protection from loss of vulnerable brain neurons to severe hypoglycemia (SH). Current research investigated whether MH preconditioning exerts sex-dimorphic effects on hippocampal CA1 neuron bio-energetic and anti-oxidant responses to SH. SH up-regulated CA1 glucose or monocarboxylate transporter proteins in corresponding hypoglycemia-naïve male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hippocampal neurons use glucose as their main source of energy. Changes in lipid levels in the central nervous system also affect the glucose metabolism of hippocampal neurons in brain areas responsible for learning and memory. Lipids also play an important role in hippocampal neuron plasticity, learning, and memory . In this study, we found that the levels of ketogenic and glycogenic amino acids (tryptophan, phenylalanine, and tyrosine), lipid intake, and glucose utilization in the internal environment of 14 DIV neurons decreased.…”
Section: Discussionmentioning
confidence: 52%
“…Hippocampal neurons use glucose as their main source of energy. Changes in lipid levels in the central nervous system also affect the glucose metabolism of hippocampal neurons in brain areas responsible for learning and memory. Lipids also play an important role in hippocampal neuron plasticity, learning, and memory . In this study, we found that the levels of ketogenic and glycogenic amino acids (tryptophan, phenylalanine, and tyrosine), lipid intake, and glucose utilization in the internal environment of 14 DIV neurons decreased.…”
Section: Discussionmentioning
confidence: 52%